The Berlin-London connection: From "No Frills" to "Full Service"? Prospects for a new bilateralism in EU affairs - Simon J. Bulmer; Roderick Parkes (Stiftung Wissenschaft und Politik (SWP), 2007)
The German and British governments have lately been making overtures at one another concerning the deepening of their bilateral cooperation in European affairs. If the two are indeed to capitalise upon Gordon Brown's political elevation, the available time frame is narrowing. The two countries' apparent dissatisfaction with their current battery of bilateral relations, and the increasing commonalities in their respective European policy agendas, might thereby appear to suffice as catalyst. In reality, the factors that previously inhibited cooperation would not necessarily be overcome. These factors, which render Britain more likely to defect from the putative bilateral cooperation than their German partners, are by no means insuperable
Keywords: 320